Business incubators in Zambia: A study of the impact on small business enterprises - Kasase, William K (Research of GSB, 2017)
This study tested the impact of Business Incubators (BI) in stimulating the growth of small to medium businesses in a Southern African country, Zambia. The study explores the existence, awareness, beliefs and experience in a sub Saharan context, identifying the key impact factors. The study was aimed at understanding whether the operation of business incubators would result in stimulating small to medium business enterprises the same way it does in the west. To achieve this, the study reviewed the existing literature on the subject matter and analysed the collected data using a questionnaire was analysed. The collected data was analysed using SSPS. The results of the analysis revealed that 64% of the respondents had heard about Business Incubators. This was done through a scientific research by a well selected set of interview questionnaires, from a sample size of 300 small to medium businesses. Only 19% confirmed receiving business assistance from a support initiative. 95% of the total respondents confirmed that a business incubator program would impact the growth of their businesses in many areas. The study further found that there were a few challenges with access to a Business Incubator. Prominent amount them was the restricted access to SMEs located in the cities. Secondly, the respondents bemoaned that the application procedure was complicated and needed to be simplified and translated into local languages. The research makes the conclusion that Business Incubators have a positive impact on the growth of small businesses in Zambia, based on the empirical evidence obtained during the study. The study revealed 32% of incubated businesses had reduced their operation costs. Contrary to available research, entrepreneurs who had received support from Business Incubators employed fewer employees than those that did not. The study therefore, questioned how business incubators increased the probability of the long term survival of the enterprise.